Parental Stress in Raising a Child with Special Needs Abroad: The Mediating Role of Financial Stress in the Relationship Between Mental Well-being and Parental Stress Among Indian Expatriate Parents in the UAE - Backer, Swaliha; Dhenwal, Sunita (International Journal of Basic and Applied Sciences, 2025)
Raising a child with special educational needs presents multifaceted challenges, which are further intensified in expatriate contexts due to cultural, economic, and systemic factors. This study explores the psychological wellbeing of Indian expatriate parents in the United Arab Emirates (UAE) who are raising children identified as Students of Determination (SOD). Specifically, it investigates the mediating role of financial stress in the relationship between parental stress and mental wellbeing. Drawing on the Family Stress Model (FSM) as the theoretical framework, the research surveyed 100 Indian expatriate parents using standardized tools to measure parental stress, financial strain, and mental wellbeing. Descriptive statistics indicated that the majority of participants experienced medium levels of stress and wellbeing. Pearson’s correlation revealed significant associations between all three variables, with financial stress positively correlating with parental stress and negatively with wellbeing. Mediation analysis confirmed that financial stress fully mediates the relationship between psychological wellbeing and parental stress. Furthermore, parents who hired personal Learning Support Assistants (LSAs) experienced significantly higher financial stress, while the presence of LSAs did not significantly impact parental stress alone. These findings underscore the critical influence of financial strain on expatriate caregivers’ psychological health and parenting capacity. The study highlights the urgent need for integrated support systems-combining inclusive educational practices with financial relief measures-to better serve migrant families navigating the complex terrain of disability caregiving abroad. Implications are discussed for school leaders, policymakers, and community health stakeholders in designing culturally responsive, equitable, and sustainable interventions for Indian expatriate families in the UAE.